Directly Dating Plio-Pleistocene Climate Change in the Terrestrial Record - Dröllner, Maximilian; Barham, Milo; Kirkland, Christopher; Danišík, Martin; Bourdet, J.; Schulz, M.; Aspandiar, Mehrooz (2023)
Accurate chronology of climatic shifts is critical to understand the controls on landscape and species evolution. Unfortunately, direct dating of continental climate change is hindered by the scarcity of dateable terrestrial products evidencing climatic shifts. Here we use ferruginous indurations from the arid landscapes of the Nullarbor Plain in southern Australia to constrain the timing of Plio-Pleistocene aridification in the continental realm. We present (U-Th)/He goethite data implying active induration processes between c. 2.7 and 2.4 Ma. Chemical-mineralogical and petrographic examination suggests that formation of ferruginous indurations was linked with a decline of the groundwater table, driven by the rapid climatic shift from humid late Pliocene to arid early Pleistocene conditions. Combined with local to global climatic proxies, we conclude that ferruginous indurations are promising targets to obtain absolute ages on landscape evolution to refine continental climatic chronology and improve understanding of the environmental drivers of species diversification and extinction.